Zooming in on the molecular characteristics of swine influenza virus circulating in Colombia before and after the H1N1pdm09 virus - Osorio-Zambrano, William F.; Ospina-Jimenez, Andres F.; Alvarez-Munoz, Santiago; Gomez, Arlen P.; Ramirez-Nieto, Gloria C. (Frontiers in Veterinary Science, 2022)
Influenza is one of the most critical viral agents involved in the respiratory disease complex affecting swine production systems worldwide. Despite the absence of vaccination against swine influenza virus in Colombia, the serologic reactivity to classic H1N1 and H3N2 subtypes reported since 1971 indicates the virus has been circulating in the country's swine population for several decades. However, successful isolation and sequencing of field virus from pigs was nonexistent until 2008, when H1N1 classical influenza virus was identified. One year later, due to the emergence of the influenza A (H1N1)pdm09 virus, responsible for the first global flu pandemic of the 21st century, it was introduced in the country. Therefore, to understand the impact of the introduction of the H1N1pdm09 virus in Colombia on the complexity and dynamics of influenza viruses previously present in the swine population, we carried out a study aiming to characterize circulating viruses genetically and establish possible reassortment events that might have happened between endemic influenza viruses before and after the introduction of the pandemic virus. A phylogenetic analysis of ten swine influenza virus isolates from porcine samples obtained between 2008 and 2015 was conducted. As a result, a displacement of the classical swine influenza virus with the pdmH1N1 virus in the swine population was confirmed. Once established, the pandemic subtype exhibited phylogenetic segregation based on a geographic pattern in all the evaluated segments. The evidence presents reassortment events with classic viruses in one of the first H1N1pdm09 isolates. Thus, this study demonstrates complex competition dynamics and variations in Colombian swine viruses through Drift and Shift.